Endoscopic Transnasal Approaches to Petrous Apex - Kovalev, Alexander; Sufianov, Rinat; Prevedello, Daniel; Borba, Luís; Mastronardi, Luciano; Ilyasova, Tatiana; Daniel, Roy Thomas; Messerer, Mahmoud; Rassi, Marcio; Zhang, Guang (Frontiers in Surgery, 2022)
Endoscopic extended transnasal approaches to the apex of the temporal bone pyramid are rapidly developing and are widely used in our time around the world. Despite this, the problem of choosing an approach remains relevant and open not only between the “open” and “endoscopic transnasal” access groups, but also within the latter. In the article, we systematized all endoscopic approaches to the pyramid of the temporal bone and divided them into 3 large groups: medial, inferior and superior - in accordance with the anatomical relationship with the internal carotid artery, and also presented their various, modern (later described), modifications that allow you to work more targeted, depending on the nature of the neoplasm and the goals of surgical intervention, which in turn allows you to complete the operation with minimal losses, and improve the quality of life of the patient in the early and late postoperative period. We described the indications and limitations for these accesses, and the problems that arise in the way of their implementation, which in turn can theoretically allow us to obtain an algorithm for choosing an access, as well as identify growth points.